PERTINENCE OF THE INDEPENDENT WORK IN THE ENVIRONMENTAL FORMATION OF THE STUDENT OF ARCHITECTURE. AN EXPERIENCE - Alonso Gatell, Aymeé (Universidad Autónoma de Tamaulipas, 2016)
For students and professors it is important the handling of the independent work as tool for the formation of the future specialist. The results reached by the students in the evaluations that carry out, manifest that it is even insufficient the time that they dedicate to the independent study. In the career of architecture, a concern is observed to achieve the student's environmental formation, identifying the independent work as a way for its concretion. The article has a objective: to expose some considerations about the relevancy of the independent work in the architecture student's environmental formation in the context of the University of Camagüey, Cuba. They were employees theoretical and empiric methods, these last ones included interviews and observation to classes. The sample included teachers and students of 3th and 4toth year, these last ones with an age 20 year-old average including both sexes. The orientation of the independent work through the different class types like organizational forms of the docent-educational process, as well as the design of a system of integrative tasks allowed an orientation toward those aholes that require of solutions. The obtained results can contribute to design an integral conception of the evaluation guided toward this purpose.